2021
DOI: 10.1002/ajhb.23591
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of skeletal age in youth female soccer players: Agreement between Greulich‐Pyle and Fels protocols

Abstract: The purpose of the study was to evaluate the agreement between the Fels and Greulich-Pyle methods for the assessment of skeletal age (SA) in female youth soccer players. Methods:The sample included 441 Portuguese players 10.08-16.73 years of age who regularly participated in organized and competitive soccer. Standardized radiographs of the left hand-wrist were obtained and analyzed by an experienced examiner. SA was estimated with the Fels and Greulich-Pyle (GP) methods. Differences between SA and chronologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…A similar trend for later maturation is also suggested among female distance runners, though data are not extensive (Malina, 2011). Skeletal maturity data for female participants in team sports are lacking, but a recent study of female soccer players showed a tendency for SA to be in advance of CA, on average, at 12 to 14 years, allowing for variation between the Greulich-Pyle and Fels methods of assessment (Martinho et al, 2020).…”
Section: Discussionmentioning
confidence: 71%
“…A similar trend for later maturation is also suggested among female distance runners, though data are not extensive (Malina, 2011). Skeletal maturity data for female participants in team sports are lacking, but a recent study of female soccer players showed a tendency for SA to be in advance of CA, on average, at 12 to 14 years, allowing for variation between the Greulich-Pyle and Fels methods of assessment (Martinho et al, 2020).…”
Section: Discussionmentioning
confidence: 71%
“…In addition, 16 of the included studies were conducted in Europe, accounting for 31.37% of the total. Specifically, there were three studies in the United Kingdom [55][56][57], two in Spain [58,59], two in Portugal [60,61], two in Italy [62,63], two in France [64,65], one in Austria [66], one in Germany [67], one in the Netherlands [68,69], one in Sweden [69], and one conducted in Denmark [70].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Regarding study design, 25 (49.02%) were observational retrospective cohort studies [23,35,40,42,43,48,50,52,54,55,57,58,[61][62][63][64][65][66][67][68][69]76,79,83,84], followed by 19 (37.25%) crosssectional studies [30,[36][37][38][44][45][46]51,53,59,60,[72][73][74][75]77,78,81,82], and 7 (13.73%) observational prospective cohort studies [39,41,55,56,70,71,80].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological maturation is a process marking progress toward the biologically mature or adult state. Although assessments of skeletal age (SA) based on the bones of the hand and wrist are generally used in a clinical context, SA is also a commonly used indicator of maturity status in studies of youth athletes [ 1 , 2 ]. An assigned SA is the chronological age (CA) at which specific stages of maturity of the hand-wrist bones are attained relative to the reference sample upon which the method of assessment was developed.…”
Section: Introductionmentioning
confidence: 99%